Geodiversity and geotourism in post-exploitation areas for the example of the Chęciny – Kielce region - Nita, Jerzy; Myga-Piątek, Urszula (Geotourism/Geoturystyka, 2025)
The article discusses the matters of management of post-exploitation areas of the Chęciny-Kielce region. Changes in surface features and other elements of the natural environment, caused by mineral exploitation of resources, are usually recognized in terms of high threat and associated with landscape devastation. The author deal with the issues of necessary protection not only of the geographical environment, but also of the landscape, especially in areas where post-mining forms do not threaten the condition of the natural environment. It presents geological values and the need to protect them in order to increase the scenic values and for the purposes of geological didactics and specialist tourism.